Digitalization and its properties based on the example of its progress in Ukraine - Oleksiuk, Roman (Global Prosperity, 2025)
Abstract. This article examines digitalization and its progress in Ukraine - the specifics of development, the main characteristics and problems of digitalization in Ukraine. Definitions of such terms as digitalization, its advantages and weaknesses in the conditions of Ukraine are given. The prospects for the development of the state in this consistent direction are also considered. The results of the analysis prove the need for the development of the state and its economic sector in the direction of digitalization.All subsequent studies in this direction should focus on the analysis of certain digitalization stages of its formation in Ukraine, each stage of its development is characterized, and the main characteristics of each of these stages are indicated, typical problems in the implementation of digitalization at the national level are indicated.An important role in the study of digitalization is played by studies that are not directly related to these concepts, but play an important role. For example, cybersecurity studies analyzed by Dulyaba N. I., Obramych O. S., who learned the theoretical foundations of digital security.The paper examines typical problems in the implementation of digitalization at the state level and studies the possible results of such implementation. It also emphasizes the need for further research in this area, the relevance and necessity of their implementation.Within the framework of digitalization in Ukraine, the following software products are considered by: “Diya”, “Helsi”, “Trembita”.